Circulating Circular RNAs as Biomarkers for the Diagnosis and Prediction of Outcomes in Acute Ischemic Stroke. Issue 1 (January 2020) - Zuo, Lei; Zhang, Lin; Zu, Juan; Wang, Zan; Han, Bing; Chen, Biling; Cheng, Mengjing; Ju, Minzi; Li, Mingyue; Shu, Guofang; Yuan, Mengqin; Jiang, Wei; et al.
Abstract : Background and Purpose—: Circular RNAs (CircRNAs) show promise as stroke biomarkers because of their participation in various pathophysiological processes associated with acute ischemic stroke (AIS) and stability in peripheral blood. Methods—: A circRNA microarray was used to identify differentially expressed circulating circRNAs in a discovery cohort (3 versus 3). Validation (36 versus 36) and replication (200 versus 100) were performed in independent cohorts by quantitative polymerase chain reaction. Platelets, lymphocytes, and granulocytes were separated from blood to examine the origins of circRNAs. Results—: There were 3 upregulated circRNAs in Chinese population–based AIS patients compared with healthy controls. The combination of 3 circRNAs resulted in an area under the curve of 0.875, corresponding to a specificity of 91% and a sensitivity of 71.5% in AIS diagnosis. Furthermore, the combination of change rate in 3 circRNAs within the first 7 days of treatment showed an area under the curve of 0.960 in predicting stroke outcome. There was significant increase in lymphocytes and granulocytes for circPDS5B (circular RNA PDS5B) and only in granulocytes for circCDC14A (circular RNA CDC14A) in AIS patients compared with healthy controls. Conclusions—: Three circRNAs could serve as biomarkers for AIS diagnosis and prediction of stroke outcomes. The elevated levels of circPDS5B and circCDC14A after stroke might be because of increased levels in lymphocytes and granulocytes. Abstract : Supplemental Digital Content is available in the text.